Neurobehavioral symptom validity and performance validity in veterans: Evidence for distinct outcomes across data types. Issue 1 (2nd January 2020) - Bomyea, Jessica; Jurick, Sarah M.; Keller, Amber V.; Hays, Chelsea C.; Twamley, Elizabeth W.; Jak, Amy J.
Abstract: Self-reported traumatic brain injury (TBI) is common in combat veterans, and identification of psychiatric and neuropsychological consequences following TBI has become a priority for veteran healthcare. Given the importance of accurately capturing symptoms potentially related to TBI in VA settings, validity metrics are frequently used to evaluate both neuropsychological testing validity and the validity of symptom self-reports. The Validity-10 of the Neurobehavioral Symptom Inventory is one such metric that was designed to evaluate symptom over-reporting and thus identify individuals who may produce inconclusive testing profiles. However, the Validity-10's ability to predict objective effort during neuropsychological testing has not been sufficiently explored in veterans. Clinical evaluation data were collected from 295 veterans seeking treatment in a VA TBI clinic. We examined whether the Validity-10 can predict invalid performance on a battery of neuropsychological tests. Validity-10 was a poor predictor of performance validity metrics. Results provide a conceptual replication of earlier work demonstrating that performance and symptom validity are divergent. As such, separate evaluation of these domains is warranted during evaluations conducted in veteran TBI populations.